Evaluasi Kesesuaian Lahan Untuk Tanaman Nenas (Ananas comosus L. Merr) Di Kawasan Bukit Kasih Kanonang Kabupaten Minahasa - Annes Febriyanti Sababalat; Diane D. Pioh; Sandra E. Pakasi (Universitas Sam Ratulangi, 2019)
ABSTRACT The study of land suitability evaluation is very needed in agriculture. The purpose of this study is to determine the suitability of pineapple fruit cultivation in the Bukit Kasih Kanonang tourist location in Minahasa Regency. This research used the field survey method. In this study land units were obtained from the results of overlapping land use maps and slope, consisting of seven land units. Document, observation, and laboratory analysis was administrated as the data collecting tech. Data analysis used matching with adjust of parameter and suitability land class until obtained suitability land map from cultivation pineapple. Classification of land suitability of pineapple plant (Ananas comosus L. Merr) in the Bukit Kasih Kanonang area with an area of 46.73/ha, spread in the marginal according class (S3) of 0.41/ha or 0.87% consisting of SPL 2 and land suitability class unsuitable class (N) area of 46.32/ha or 99.13% consisting of SPL 1, SPL 3, SPL 5, SPL 6, SPL 7 with limiting factors in soil texture, slope, soil depth and rainfall rain. Keywords: Evaluation, Land Suitability, Pineapple.